Differential Circulating Levels of Naturally Occurring Antibody to α-Synuclein in Parkinson’s Disease Dementia, Alzheimer’s Disease, and Vascular Dementia - Wang, Jian; Zheng, Bo; Yang, Shu; Hu, Mei; Wang, Jian-Hong (Frontiers in Aging Neuroscience, 2020)
Background Aggregation of alpha-synuclein (α-syn) is considered to be a significant pathological hallmark and a driving force of Parkinson's disease (PD). PD dementia (PDD) occurs in a substantial number of PD patients. Naturally occurring antibody against α-syn (NAb-α-syn) exist ubiquitously in human blood and is reported to be altered in PD. However, it is not clear yet whether PDD had similar changes of circulating NAb-α-syn. Methods In this study, we recruited 61 PDD patients, 52 patients with Alzheimer’s disease (AD), 51 patients with vascular dementia (VaD) and 50 normal controls (NC). ELISA was used to examine NAb-α-syn levels in serum. Results In comparison with NC, serum levels of NAb-α-syn were significantly lower in patients with PDD. However, serum levels of NAb-α-syn were comparable among AD, VaD and NC group. Serum levels of NAb-α-syn were positively correlated with the cognitive function, as reflected by MMSE and MoCA. Serum levels of NAb-α-syn were negatively correlated with the severity of PD (as reflected by UPDRS) and the duration of PD and PDD. Serum NAb-α-syn can differentiate PDD patients from AD and VaD patients. Conclusion These results suggest circulating NAb-α-syn might be a potential.